THU0174 Comparison of Switching to Reduced Dose VS Continuation of Standard Dose Etanercept for Rheumatoid Arthritis Patients in the Corrona Registry. (10th June 2014) - Greenberg, J.D.; Shan, Y.; Reed, G.W.; Bitman, B.; Collier, D.
Abstract : Background: Both patients and doctors are interested in information exploring the lowest effective dose of a drug. Clinical trials have recently demonstrated that the achievement of low disease activity (LDA) or remission with anti-TNFs may be sustained in a subset of RA pts prescribed anti-TNFs at reduced dosages. However, little is known regarding the frequency of this practice or clinical outcomes in a real-world U.S. population. Objectives: To compare rates of achieving sustained LDA (or remission) for patients on reduced dose versus standard (Std) dose etanercept (ETN) among pts who previously achieved LDA (or remission) on Std dose ETN. Methods: Among 36, 328 RA pts enrolled in the CORRONA registry, there were 6, 946 patients receiving ETN during the follow-up period. We defined Std dose as pts on ETN 50 mg qwk or 25 mg biw, and reduced dose as <50 mg qwk (or equivalent as most pts dosed 50 mg longer than a week) reported on ≥2 study visits at least 3 months apart. We identified two study cohorts. The index date was defined as the time at which patients achieved either LDA (LDA Cohort) or remission (Remission Cohort) on ETN. We imputed non-response for patients who changed the ETN dose (from reduced to Std) or switched biologics. For pts censored, we used LOCF for the last CDAI value prior to censoring. We calculated odds ratios using multivariable logistic regression for both sustained LDA and remission, including covariates differing (p<0.2) between reduced and Std dose. Results: At index date, there were 592 pts who had achieved LDA on Std dose and 93 achieved LDA on reduced dose. Reduced dose pts were significantly older (57.2 vs 53.6 yrs), had lower mean CDAI at index (2.8 vs 4.6), were less likely to be RF+ (66% vs 78%), less likely to be prescribed with non-biologic DMARD (54% vs 78%) and less likely to take prednisone (11% vs 22%). For the remission cohort, there were 242 on standard and 47 on reduced dose ETN, with similar trends between groups (reduced vs Std dose) as the LDA cohort. The adjusted odds ratio (OR) for sustaining LDA for reduced vs Std dose was 0.62 (95% CI 0.21-1.80, p-value 0.38) at 6 months and 0.16 (95% CI 0.07-0.36, p-value <0.001) at 12 months. The OR for reduced vs Std dose for sustaining remission was 1.21 (95% CI 0.36-4.06, p-value 0.76) at 6 months and 0.64 (95% CI 0.21-1.90, p-value 0.42) at 12 months. Conclusions: After achieving LDA or remission on standard dose ETN, reducing the ETN dose demonstrated comparable effectiveness for a period of 6 months but not at 12 months for LDA. Comparable effectiveness for remission was observed at 6 and 12 months. Caveats include the non-randomized nature of the study and in the reduced dose group the small number of patients and the lower disease activity scores at baseline. References: Smolen et al. Maintenance, reduction, or withdrawal of etanercept after treatment with etanercept and methotrexate in patients with moderate rheumatoid arthritis (PRESERVE): a randomised controlled trial. Lancet. 2013 Mar 16;381(9870):918-29. Acknowledgements: The CORRONA RA registry has been supported through contracted subscriptions in the last two years by Abbvie, Amgen, AstraZeneca, Genentech, Horizon Pharma, Eli Lilly, Novartis, Pfizer, Vertex and UCB. Disclosure of Interest: : J. Greenberg Shareholder of: CORRONA, Inc., Consultant for: AstraZeneca, Pfizer, Employee of: CORRONA, Inc., Y. Shan Employee of: CORRONA, Inc., G. Reed Employee of: CORRONA, Inc., B. Bitman Shareholder of: Amgen, Employee of: Amgen, D. Collier Shareholder of: Amgen, Employee of: Amgen DOI: 10.1136/annrheumdis-2014-eular.1836